Physical Activity Messaging on North American Jewish Day School Websites. Issue 3 (2nd July 2020) - Kahan, David; McKenzie, Thomas L.; O'Brien, Anna; Portillo, Carlos; Sprague, Remy; Marchant, Emma; Lising, Nadine
ABSTRACT: Studies of Jewish day schools' websites regarding opportunities for students to engage in physical activity (PA) have not been published. We analyzed the content of 516 North American Jewish day schools' websites in 237 cities to ascertain mentions of sports (i.e., interscholastic) and PAs (e.g., intramural sports, PA clubs) and to determine how their prevalence differed by school religiosity, composition, and level. Overall, 41% and 45% of websites mentioned at least one sport and PA, respectively. Liberal (vs. Orthodox and Haredi), coeducational (vs. single sex), and schools with secondary grades (vs. elementary only) mentioned proportionately more sports, PA, or both.